Metformin From Diabetes Management to Broader Applications in Weight Reduction and Metabolic Health - Zapasek, Daniel; Słowik, Julia; Bajak, Mateusz; Szczepański, Michał; Mamczur, Maciej; Kuliga, Marcin; Inglot, Julia; Inglot, Jadwiga; Feret, Dominik Maciej; Sowa, Damian (Quality in Sport, 2024)
Introduction Metformin is a widely used oral hypoglycemic agent for type 2 diabetes, with origins in medieval European medicine through the use of Galega officinalis. Subsequent centuries of research led to the development of synthetic biguanides, with metformin’s approval as an antidiabetic agent in 1957. Since then, its therapeutic applications have broadened to address other metabolic and endocrine disorders, such as obesity, polycystic ovary syndrome (PCOS), and antipsychotic-induced weight gain. Purpose of the Study This study aims to review metformin’s pharmacological properties, mechanisms of action, and its expanded clinical applications. Specifically, it focuses on metformin’s role in promoting weight loss and improving metabolic health across diverse patient populations, including those without diabetes. The study also addresses evidence gaps and proposes areas for further research on dose optimization and safety in non-diabetic populations. Materials and Methods A systematic literature review was conducted using databases such as PubMed and Google Scholar, focusing on studies examining metformin’s effects on glycemic control, weight reduction, and metabolic stability. Conclusions Metformin’s history underscores its evolution from traditional remedies to a versatile pharmacological agent for treating diabetes and other metabolic conditions. Ongoing research is essential to fully establish its optimal therapeutic parameters and long-term safety for diverse patient groups.